ANALISIS GAYA KEPEMIMPINAN DALAM MENINGKATKAN MOTIVASI KERJA DI PERUSAHAAN INTERNATIONAL BUSINESS FUTURES (IBF) TRADER - Siti Aminah; Alda Ramadhika (Yayasan Insani Mandiri Santani, 2025)
The purpose of this study was to see how manager/leader leadership styles impact employee work motivation in International Business Futures (International Business Futures (IBF)) Traders. In the dynamic digital commerce industry, leadership is essential to create a productive work environment and support employee morale. This study uses a qualitative approach with a descriptive method, where data is collected through in-depth interviews, observations, and documentation of managers and employees at IBF Trader. The results of the study show that IBF Trader uses a situational leadership style, which combines authoritarian, supportive, and transformational leadership styles according to the needs of the organization and employees. Managers act as assertive leaders in providing direction, but managers are also able to build supportive and teaching relationships with employees. Employee work motivation is enhanced through a combination of a performance-based reward system and a personalized approach to understanding individual needs. The conclusion of this study found that a flexible and flexible leadership style increases employee work motivation. By implementing the right leadership strategy, companies can create a better work environment, improve employee performance, and better achieve organizational goals. Keywords: Leadership Style, Work Motivation, Situational Leadership.